Preliminary Investigations into Using Eugenol to Recover Erased Characters on Polymers - Burke, Karl; Lewis, Simon; Bett, J.; Southurst, T.; Lim, K.; Gutowski, S. (International Association for Identification, 2007)
In this paper we present our preliminary studies on the efficacy of eugenol for the recovery of erased characters on polymers. We have found that eugenol rapidly recovers erased characters when applied to the surface of polymer substrates. By applying eugenol to the surface to be treated using a cotton bud or paintbrush, we were able to revisualize erased characters from a range of polymers, inclluding acrylonitrile butadiene styrene, acrylic, high-impact polystrene, and polystyrene. Eugenol is safe, nonhazardour, and easily sourced reagent for this purpose.